A study on victims of road traffic accidents attending casualty in a tertiary care hospital, Khammam - Neeluri, Rajesh; Anga, Venkata Suresh (International Journal Of Community Medicine And Public Health, 2018)
Background: As per global status report on road safety 2015, 1.25 million road traffic deaths occurred every year. Most common cause of death among those aged 15-29 years was road traffic accidents. The objectives of the study were to study the socio-demographic profile of the victims of road traffic accidents, to identify the risk factors responsible for road traffic accidents and to identify the various presenting injuries of road traffic accident victims. Methods: It was a Hospital based cross sectional study. Victims of road traffic accidents attending casualty during July 2011 – June 2012 were studied. A pretested semi structured questionnaire was administered. A total of 280 road traffic accident victims were interviewed during the study period. Data was entered in Microsoft excel sheet and analyzed using Statistical Package for Social Sciences (SPSS) version 20. Results were expressed as proportions for different study variables. Results: Out of the 280 victims, majority 206 (73.57%) of study participants were males. The highest numbers of victims (34.20%) were between 21-30 years of age group. 40.71% were using two wheelers. Most of the accidents took place in the evening (6 pm to 12 am) i.e. 39.10%. Most common site of presenting injury was lower limb (40.71%). In this study 22.5% were under influence of alcohol while driving. Conclusions: Road traffic accidents were more in young age groups and in males. Road safety education should be promoted.